Statistically strongly regular matrices and some core theorems - M. Mursaleen; Osama H. H. Edely (International Journal of Mathematics and Mathematical Sciences)
We define the statistically strongly regular matrices analogous to the strongly regular matrices, and further we use these matrices to establish necessary and sufficient conditions to prove some core theorems.